Comparative Literature Studies in Violeta Kelertas’s Literary Criticism - Jurgutienė, Aušra (Colloquia, 2025)
The article examines Violeta Kelertas’s comparative research in the context of the Lithuanian diaspora in the United States. After WWII, comparative studies of Lithuanian literature on both sides of the Atlantic continued the tradition of comparative historical studies inherited from the interwar period and were developed as an addition to the history of national literature. However, Kelertas and some other diaspora literary critics methodologically renewed comparative literature more than their counterparts in Lithuania. The fundamental shift in comparative literature in the US—from the French tradition to postmodern comparative literature—was also influenced by its thematic, feminist, and postcolonial comparative studies, which enabled Lithuanian literature to raise new questions and introduce it into the global context of literary studies and connections with new thematic aspects. The article argues that comparative literature studies were carried on in the Lithuanian diaspora. In Kelertas’s case, comparative research in literature was modernized through feminist and postcolonial approaches.